Rural landscape characterization from the perspective of the tourist using online reviews: A case study of Yayou Gou Village in Shandong, China - Zhuang, Qianda; Hussein, Mohd Kher; Mohd Ariffin, Noor Fazamimah; Mohd. Yunos, Mohd. Yazid; Chen, Shuzhen (Frontiers in Environmental Science, 2022)
In the field of landscape characterization, it is difficult to obtain tourists’ various perceptions of a landscape. To overcome such drawbacks, online available reviews and comments from tourists can be utilized as an alternative way to landscape characterization. This study examined the rural landscape characterization in Yayou Gou Village, a unique and attracting combination Shandong China. A qualitative content analysis was undertaken on tourists’ comments and reviews of Yayou Gou Village on tourist websites and social media platforms including Qnar, Meituan, Ctrip, Dianping and Sina Microblog. Nvivo 12 was used for the content analysis and qualitative coding. A variety of natural, cultural and social, perceptual and seasonal characteristics of rural landscape as well as facility and infrastructure were revealed. Cultural and social landscape characters including performance landscape and festival activities, building, educational and home-stay landscape, diet landscape and night landscape, are obviously richer than other aspects in this rural village. Natural, perceptual and seasonal landscape characters are not fully exploited for rural tourism and landscape. This study suggested natural, cultural and social rural landscape, and facility and infrastructure were influenced by spatial, seasonal and perceptual dimensions. Suggestions for better landscape conservation and management can be acquired through the characterization process. This study provided an innovative approach for landscape characterization with online review data from various tourists. It demonstrated that online social media data contain abundant information about landscape that they have visited and could be well used for exploring the landscape characters in rural areas.